Effect of visual search training on quality of life and visual performance: a systematic review - Faris Khairuddin Syah; Diah Kurnia Mirawati; Pepi Budianto; Hanindia Riani Prabaningtyas; Raden Andi Ario Tedjo; Muhammad Hafizhan; Taufiq Wildan Laksono; Amalia Fitri Puspitasari; Muvida Muvida; Muhammad Yusuf Brilliant Pradana (Published by Universitas Gadjah Mada, 2026)
Homonymous hemianopia is a common and debilitating complication of post-chiasmal brain injury. Visual search training (VST) is a common compensation strategy used to improve object detection in the blind visual field. This review aims to synthesize the evidence regarding the effects of VST on quality of life, visual performance, and the characteristics of intervention protocols used across studies. This systematic review included randomized controlled trials, cohort studies, and quasi-experimental studies. Eligible studies were screened and data were extracted independently, and the risk of bias and intervention protocolswere assessed. Eight studies met the eligibility criteria. Visual search training and related visual rehabilitation interventions are generally well tolerated, with no major safety concerns identified. Reported adverse events were predominantly mild, transient, and non-physical, and were more commonly associated with comparator interventions or logistical aspects of participation. More information on safety monitoring and standardized protocol is needed in future trials.